REPRESENTASI PEREMPUAN DALAM SINEMA FIKSI ILMIAH: INTEGRASI FEMININ-MASKULINI DALAM PEMBANGUNAN KARAKTER NEYTIRI DALAM SERI FILM AVATAR - Eva Nurrahmi Lukman; Badrizal AlHazar (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study examines the representation of women in science fiction cinema through the character of Neytiri in the Avatarfilm series, with a particular focus on the integration of feminine and masculine attributes in public, domestic, and relational roles. While science fiction films have traditionally emphasized masculine dominance and positioned female characters within symbolic or subordinate roles, this research explores how Avatar offers a more complex construction of female agency. Using a qualitative approach with film text analysis, the study analyzes key scenes, dialogues, and visual representations of Neytiri across Avatar (2009), Avatar: The Way of Water (2022), and Avatar: Fire and Ash (2025). The analysis is informed by gender performativity theory and feminist film studies to identify how feminine and masculine attributes are constructed and integrated within narrative contexts.The findings indicate that Neytiri is consistently represented as an active subject of moral, strategic, and physical authority, while simultaneously performing maternal roles, family protection, and social leadership. Feminine attributes such as empathy, emotional expressiveness, and relational care coexist with masculine attributes including strategic leadership, decisiveness, and defensive violence, without hierarchical dominance. The longitudinal analysis reveals a significant character development, particularly in Fire and Ash, where maternal grief transforms into strategic and political action. This integration challenges binary gender constructions and highlights gender as performative, fluid, and context-dependent. The study contributes to gender and film studies by proposing feminine–masculine integration as an analytical framework and by demonstrating the relevance of cinematic representations to contemporary social contexts, particularly in relation to women’s roles and leadership